1988
DOI: 10.1002/pola.1988.080261207
|View full text |Cite
|
Sign up to set email alerts
|

Phthalonitrile‐based high temperature resin

Abstract: An aromatic, diether‐linked phthalonitrile resin, prepared from 4,4′‐bis(3,4‐dicyanophenoxy)biphenyl, exhibits excellent thermo‐oxidative properties. The resin is easily processed from the melt of the monomer in a controlled manner as a function of the amine curing agent and processing temperatures. Polymerization occurs by a cyclic addition reaction without the formation of volatile by‐products. The polymerization reaction can be stopped at a prepolymer stage. The prepolymer can be stored indefinitely at ambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
167
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(170 citation statements)
references
References 6 publications
0
167
0
1
Order By: Relevance
“…These resins have been considered as an ideal material for applications in various fields such as marine, aerospace and electronic uses [4][5][6][7][8]. However, the conventional phthalonitriles have the problem of poor processability resulting from their unexpected properties such as high curing temperature, long curing time and narrow processing window (temperature between the melting point and the polymerization temperature) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These resins have been considered as an ideal material for applications in various fields such as marine, aerospace and electronic uses [4][5][6][7][8]. However, the conventional phthalonitriles have the problem of poor processability resulting from their unexpected properties such as high curing temperature, long curing time and narrow processing window (temperature between the melting point and the polymerization temperature) [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Poly (arylene ether nitrile) (PEN), one of the highperformance engineering thermoplastics, has been widely used in microelectronic industry, aerospace, electrical insulation, and semiconductor industries due to its outstanding properties such as high thermal stabilities, high thermooxidative stabilities, excellent mechanical and chemical inertia [1][2][3][4][5][6][7][8]. Despite the advantages of the PEN, the integrated circuit need low dielectric constant materials at high frequency [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various bisphenols have been studied for synthesis of PEN via nucleophilic aromatic substitution polymerization, these PEN materials exhibit excellent thermal stabilities over a wide-range of temperature [1][2][3][4][5][6]. The cyano group serves as a potential site for crosslinking reaction and can make polymer transform from thermoplastic to thermosetting [7][8][9][10][11]. Matsuo et al [3] systematically studied the synthesis of 2,6-dihalobenzonitrile with different kinds of bisphenol including the 4,4'-dihydroxybiphenyl and found that mechanical properties of biphenylbased PEN were better than that of the corresponding ketone or sulfone containing polymers.…”
Section: Introductionmentioning
confidence: 99%